GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 649923430 species occurrences available in GBIF matching the query: All data. The dataset includes 649923430 records from 13764 constituent datasets: 19 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 1309 records from Mongolian Plant (MMNH-PL). 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 12 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/4 (ANDEEP II). 163 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 103875 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Hildener Heide - Spörkelnbruch (Haan). 355394 records from Invertebrate Paleontology Division, Yale Peabody Museum. 21 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JANUARY-1995-D4. 504 records from Range table from benthic foraminifers in ODP Hole 172-1057A. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 52171 records from Bryophyte Collection - University of Washington Herbarium (WTU). 1555 records from Countryside Council for Wales - Bat Roosts Database - Pembrokeshire. 1 records from Karpfenteich, Klasse 6d. 144 records from BIRDRACE Die Mohrenlerchen. 16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT008_5-CTD42. 6290 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 3945 records from TTRS Ornithology. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 202 records from Total foraminifera counts of multinet M6/7_MSN96. 4 records from Microzooplankton abundance and biomass at station TT050_17-4. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 1 records from Miriapodi di alcune grotte della Campania. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 75 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 59 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211630-9. 109 records from Phytoplankton abundance at station CD46_1305C#2. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2161-1. 36 records from Pollen profile ADR309. 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 9 records from Analyses of the recent components of sediment core PS1013-1. 410 records from Gemeindegebiet Weikendorf (Marchfeld). 685 records from Planktic foraminifera abundance of Hole 4-30. 122 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 68 records from Range table from benthic foraminifers in ODP Hole 149-897C. 36 records from Range table from benthic foraminifers in ODP Hole 160-967E. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 45 records from Nannofossil abundance of Hole 64-481A. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 1614 records from Culture Collection of Algae. 3002 records from Colección de Peces Universidad Católica de Oriente. 480 records from Spiders of French Guiana. 263 records from Artenvielfalt Kreis Gießen. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 78 records from Phytoplankton counted on two fractions of surface sediment samples from Meteor stations M35003-4 to M35010-3. 1942 records from Spiders of Ireland. 15 records from Nannofossil abundance of Hole 1-3. 36 records from Nannofossil abundance of Hole 5-34. 81 records from Plasm bearing foraminifera counts of multinet SO118_MSN1251. 44 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 2 records from Nannofossil abundance of Hole 66-491. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 2 records from Nannofossil abundance of Hole 4-26. 180 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Anfibios. 4830 records from (Table 5) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-905A. 13 records from Planktic foraminifera abundance of Hole 47-398A. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 17 records from Schutzgebiet Ochtersum. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 34 records from Diatom assamblage in samples from sediment trap OG3. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 10 records from Ostracoda abundance of Hole 44-390. 2599 records from (Table A1) Ostracoda abundances in sediment core GIK23414-9. 536 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747. 570 records from Colección de Flora Ficológica Marina de Tamaulipas, México (UANL). 323 records from Southern Ocean Cnidarian Collections. 67 records from (Table 7) Distribution of early to middle Eocene calcareous nannofossils in ODP Hole 149-900A. 650 records from (Figure 3) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-635B. 86 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 57 records from Relative abundance of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 26 records from Occurrence of mammalia relicts at site Predmosti. 28 records from Korean Plant Virus Database. 30178 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Bag Seine. 608 records from Distribution of planktic foraminifera in sediment core GIK16396-1. 332 records from Foraminifera distribution of sediment core SDSE192. 43 records from Dinoflagellate abundance of Hole 14-137. 1735 records from Naturalis National Natural History Museum (NL) – Acari_Types. 33 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from the Temburong River basin, Brunei Darussalam, Borneo.. 81 records from Distribución del gecko introducido Hemidactylus frenatus (Dumeril y Bribon 1836) (Squamata: Gekkonidae) en Colombia. 1481 records from Reptilia notes, NTNU, Trondheim. 2160 records from (Table 8B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 5-2 through 8-4. 615 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from Abundance of benthos infauna at station PO128/2_267. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 415 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 3420 records from Harvestmen of French Guiana. 83 records from Spechtwald. 142 records from Phytoplankton abundance at station CD47_1206C#7. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_1, Casma, Peru. 23801 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 13884 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 429 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V32-128. 6 records from Two new species of Aleocharinae (Coleoptera, Staphylinidae) found in fungus gardens of Odontotermes termites (Isoptera, Termitidae, Macrotermitinae) in. 15785 records from Birds (KIEE-BI). 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 6327 records from Planktonic foraminifera in ODP Hole 160-963A. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 3184 records from Herbarium specimens of Limoges university (LIMO). 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 1 records from Myriopoden von Epirus. 15 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 17-165. 397 records from Planktic foraminifera counts of sediment core V29-29. 127 records from BIRDRACE Southernmost Lakers. 70 records from Korean Aquatic Vascular Plants. 5056 records from Nest census, Windmill Islands 2002/03. 17 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (2000m section). 63 records from Museu Paraense Emilio Goeldi - Ricinulei Collection. 23 records from (Table 2) Relative abundance of coccoliths at DSDP Hole 75-530A. 1196 records from Entomological collection of the National Museum. 227 records from Total foraminifera counts from multinet M31/3_MSN918. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 96 records from BIRDRACE Emslandracer. 157 records from Total foraminifera counts from M35/1_MSN1069. 3526 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 10 records from Microzooplankton abundance and biomass at station TT043_15-1. 174 records from (Table 5) Absolute abundances of planktonic foraminifera in Maastrichtian to upper Thanetian sediments of DSDP Hole 43-384. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 29171 records from Naturalis Biodiversity Center (NL) - Collembola. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 215 records from Total foraminifera counts from multinet M31/3_MSN921. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 124 records from Total foraminifera counts of multinet M10/2_MSN317. 78 records from Total foraminifera counts of multinet M12/3_MSN541. 348 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 69 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1379. 52 records from Foraminifera species abundances from tow TT007_7-MOC13. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 3 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 431 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C. 601 records from LBV 100 - Artenvielfalt am Rothsee. 29 records from Range table from ostracoda in ODP Hole 151-911A. 85 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 42 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 5681 records from Alga (KIWE-AG). 601495 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 8200 records from KNWR Entomology Collection. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 1426 records from Korean Insect Database. 14165 records from NYSM Mammals. 617 records from (Table 5) Realtive abundance of planktonic foraminifera in sediment core AHF-11343. 188 records from Frauenholz (Holzmaden). 34 records from Planktic foraminifera abundance of Hole 47-398. 11 records from A new species of Probolomyrmex from Madagascar.. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 169 records from Schulgelände des Schulzentrums am Himmelsbarg. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 234 records from Werremündung im Schwarzatal. 19 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 1797 records from Range table from benthic foraminifers in ODP Hole 149-898A. 1 records from Collection Mammalia fossil SMF. 5363 records from Colección Ornitológica de la Universidad del Valle. 132 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 76124 records from Lichen field notes, Oslo (O). 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 1861 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 1848 records from (Figure 8) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-632A. 13 records from Meiobenthos investigations in the Black Sea during Poseidon cruise PO317/3. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1220-3. 3550 records from UCM Fish Collection (Arctos). 18 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 54 records from Range table from benthic foraminifers in ODP Hole 159-961A. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 1029 records from Freshwater plants of Cameroon. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 9 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 29 records from Foraminifera species abundances from tow TT011_3-MOC60. 5 records from Phytoplankton abundance at station Rigel_6_2005-08 in August 2005, Chipana, Chile. 14 records from Nannofossil abundance of Hole 10-97. 29 records from Nannofossil abundance of Hole 73-523. 1 records from Occurrence of mammalia relicts at site High Furlong. 118 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 432 records from Foraminifera abundance of Hole 60-454. 1101 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 1603 records from Hare Survey of Ireland 06/07. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 1746416 records from SA Flora (BDBSA). 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 205 records from Total foraminifera counts of multinet M6/7_MSN119. 300 records from (Table 2) Occurrence of ostracoda in sediment core PS2200-5. 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Plantas vasculares. 603 records from Diatoms from the Vestfold Hills Lakes. 17520 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 17715 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 1798 records from Aggregate Industries - Grassland and Heathland Survey at Bardon Hill 2008/9. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 64 records from VFD-RP, Taunus: Bergweide Dehe. 19 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 331 records from (Table 2) Benthic foraminiferal genera in DSDP Core 95-612-37-3. 1391 records from Lichen herbarium, NMBU. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 457 records from Microbial Observatory of the Laboratoire Arago. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 79 records from Total foraminifera counts from M35/1_MSN1049. 49 records from Total foraminifera counts of multinet M10/2_MSN251. 148 records from Total foraminifera counts of multinet M21/2_MSN638. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 353 records from Size of planktic foraminifera at CTD station PS55/063. 131 records from BIRDRACE Brut. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 30 records from Nannofossil abundance of Hole 94-608. 1100 records from Pinos del Noreste de México (UANL). 146 records from Total foraminifera counts of multinet PO247/2_MSN1374. 3 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 242 records from Schieferbrüche. 12 records from Meiofauna abundance in sediment core 13200-046. 4 records from Sarcodine counts and carbon biomass at station TT012_4-CTD6. 225 records from (Table 2) Planktic foraminiferal species and number of specimens present in 5 cc of sediment per sample at DSDP Site 77-540, Late Cretaceous. 16 records from Diatom abundance measured on water bottle samples at station PS58/088-4. 1122 records from (Figure 2) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-762B. 3259 records from Florística de áreas protegidas en el estado de Durango. 17071 records from UAM Invertebrate Collection (Arctos). 361 records from Stable isotopes and content of foraminifera at Hole 130-805C. 679 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 173 records from Collection Crustacea NHCY. 33 records from Familientag am Schorberg. 661 records from 녹조류 DB. 6680 records from SOMBASE PYCNOGONIDS. 51 records from (Table 1) Total cyst counts and concentrations of dinocysts and pollen together with environmental parameters. 7 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE236. 210 records from (Table 1) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-651A. 138 records from Fig. 3. Pollen counts of the PG1756 core from Lake Billyakh. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 29128 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 1 records from Hoplophora testudinea. 842 records from Marine specimens of Misaki Marine Biological Station, School of Science, University of Tokyo. 18 records from (Table 3) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897C. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 6323 records from Canadian National Collection of Insects. 40 records from Nannofossil abundance of Hole 47-398. 21 records from Description of lithologic section units of IODP Hole 325-M0042A. 1 records from Occurrence of mammalia relicts at site Raagelund. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 819 records from CABI Bioscience Nematode Collection. 536 records from Planktic foraminifera abundance of Hole 14-141. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 355 records from Culture Collection of Cryophilic Algae. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 19 records from Glemstal (Leonberg). 9 records from Coccolith counts of multinet M32/5_MSN981. 11 records from Nannofossil abundance of Hole 10-86. 9281 records from Distribution of planktic foraminifers of core V30-40. 778 records from Benthic foraminifera abundance of Hole 84-567A. 108 records from Phytoplankton abundance in surface water in May 1996, Chimbote, Peru. 5 records from Nannofossil abundance of Hole 29-278A. 194898 records from Naturalis Biodiversity Center (NL) - Coleoptera. 1655 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire REPTILE Records 1950-2007. 1532 records from (Table A5) Distribution of planktic foraminifera and sea surface temperature reconstruction of sediment core V30-97 in the North Atlantic. 2682 records from Foraminifera distribution of sediment core KET80-03. 104 records from Urwald 1 (Bad Waldsee). 24 records from Occurrence of mammalia relicts at site Kartstein. 16 records from Occurrence of mammalia relicts at site Nazeing. 22 records from Planktic foraminifera abundance of Hole 51-417. 258 records from Planktic foraminifera abundance of Hole 67-500. 400 records from Planktic foraminifera abundance of Hole 32-310. 666 records from (Tab. 4) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hill. 88 records from Gymnicher Mühle. 9 records from Nannofossil abundance of Hole 11-99A. 14 records from Range table from ostracoda in ODP Hole 160-967A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 61 records from BIRDRACE Bergische Ornis. 2330 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 1623 records from Censo de primates de la Fundación Entropika. 8 records from Two new species of Scymnini (Coleoptera: Coccinellidae) from Karnataka, India. 31339 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 150 records from LAGPLON - Polynésie francaise. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 150 records from Total foraminifera counts of multinet M12/3_MSN533. 13750 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 2 records from Nannofossil abundance of Hole 1-4. 174 records from Occurrence of mammalia relicts at site Velika Pecina. 6950 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 1656 records from USGS SESC - Everglades - Herpetofauna - 2000-2002. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 9 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 69 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 654 records from (Appendix A) Dinoflagellate counts in surface sediments of cores taken in the North Pacific. 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 4293 records from Benthic foraminifera abundance of Hole 84-570. 19 records from Contribution to the Central European Gymnodamaeus species G. barbarossa and G. bicostatus (Acari, Oribatida, Gymnodamaeidae. 4722 records from HVAT - Herbário do Vale do Taquari. 814 records from Biological Records Centre - Orthoptera and Allied Insects of the British Isles data from iRecord. 9684 records from Fish collection, Natural History Museum, University of Oslo. 268891 records from MVZ Herp Collection (Arctos). 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 20727 records from Arctic Species Trend Index (ASTI) : Terrestrial. 1 records from Microplankton counts and carbon biomass at station TT011_15-CTD168. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 904 records from Red list project inventory, vascular plants. 8 records from Diatom abundance measured on water bottle samples at station PS58/041-2. 9140 records from IICT Colecção Zoológica. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 2546 records from Nature Locator - PlantTracker data from 2012 onwards. 4 records from Results of diatom analysis of Hole 302-M0004A. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 51181 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 29 records from Naturerfahrung. 146 records from LK 11 im Mönchspark. 88 records from BIRDRACE Kingfisher. 152 records from Plasm bearing foraminifera counts of multinet SO118_MSN1252. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 75 records from Faunal assemblage of sediment core GS7603-9. 139641 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 1016 records from Diversidad de los coleópteros Scarabaeiodea del estado de Puebla (II). 66 records from The genus Dichopygina gen. n. (Diptera: Sciaridae). 8 records from Trap data WR2, 599 m. 3 records from Sarcodine counts and carbon biomass at station TT011_12-CTD150. 341 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 2 records from Nannofossil abundance of Hole 6-50A. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 15 records from Phytoplankton abundance along the track of Akademik Vernadsky cruise AV5. 1 records from Simopone yunnanensis sp. nov. – the first record of Simopone Forel, 1891 from China (Hymenoptera, Formicidae, Cerapachyinae). 106550 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 48566 records from North West Territories and Nunavut Bird Checklist, Canada. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 65 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 517 records from Range table from benthic foraminifers in ODP Hole 143-865A. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 140 records from BIRDRACE Guckers Offenbach. 54 records from (Table 3) Range chart of calcareous nannofossils from Weddell and Bellingshausen Sea sediment cores. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 215 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 115 records from (Table 2) Abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 300 records from (Table 1) Stable oxygen and carbon isotopes, and relative abundances, of selected planktonic foraminiferal species together with biogenic compounds in the surface sediment samples retrieved during the SO-184 cruise off Wand SW Indonesia. 1 records from Palynological investigation of surface sample of profile Tso Kar. 964 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 85 records from RSPB - Black grouse lek survey in Ross-shire. 119 records from Palynology of a sediment profile from Lake Voulkaria in Greece. 3538 records from Anfibios del Estado de Veracruz.. 2093 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 237 records from Collection Mammalogie - SNSD. 36116 records from Fish Collection of Yokosuka City Museum. 36 records from UC Davis Department of Anthropology Museum. 74 records from Planktic foraminifera abundance of Hole 62-465A. 6 records from Range table from benthic foraminifers in ODP Hole 178-1095B. 12 records from Oberservation of birds at station PS14/158 along 49° West. 14741 records from Trekvis - Migratory fishes in the river Scheldt. 96 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 198-1207A. 34 records from Levantamento de Herbáceas da RDS Uatumã. 2050 records from Birds (ENHM-BI). 111 records from (Figure 3) Foraminiferal assemblages recovered from DSDP Hole 79-547B. 100 records from Brock University Herbarium (BU). 702 records from HSU Vertebrate Museum Reptile Collection. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 138 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 114203 records from UTA Herpetology. 433 records from Planktic foraminifera abundance of Hole 22-214. 1 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 212 records from Artenvielfalt im Beckerbruch (Dessau). 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 1698 records from Distribution of planktic foraminifers of core RC10-62. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 17672 records from LSUMZ (LSU MNS) Fishes Collection. 4 records from Range table from planktonic foraminifers in ODP Hole 171-1049A. 607 records from (Table 3) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-590 in the southwest Pacific. 43 records from Hertfordshire Biological Records Centre - HBRC Wildlife Site Surveys, Hertfordshire. 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 9 records from A new species of the loricariid catfish genus Hemipsilichthys from southern Rio de Janeiro coastal rivers, southeastern Brazil (Teleostei: Siluriformes).. 201 records from Seawater carbonate chemistry and processes during experiments with coccolithophores (Emiliania huxleyi and Gephyrocapsa oceanica), 2000. 1210 records from Earthworms of Ireland. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 3 records from Nannofossil abundance of Hole 31-301. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 3910 records from Plant (MNHM-PL). 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 313949 records from United States National Plant Germplasm System Collection. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 164 records from Planktic foraminifera abundance of Hole 22-215. 26 records from Planktic foraminifera abundance of Hole 20-200A. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 3 records from Microfossil abundance of Hole 50-415. 8857 records from Artròpodes d'Andorra. 17618 records from BioGIS - Mammals - INPA database. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 1 records from Waldtag in und um Seelingstädt. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 1 records from Oribates calcaratus. 71 records from (Data S1) Palynology of ODP Site 113-696. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 70432 records from National Bat Database of Ireland. 13 records from FND "Weißer Berg" Leißling. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 209 records from Relative abundance of coccosphere-units at site GIK23414. 16 records from Coccolith counts of multinet M32/5_MSN986. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 126 records from Total foraminifera counts from M35/1_MSN1050. 451 records from Nannofossil abundance of Hole 15-148. 21 records from Nannofossil abundance of Hole 6-55. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 2427 records from Ibaraki Nature Museum, Mollusk collection. 14137 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 646 records from Engraulidae-Clupeidae. Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 300 records from Plant (SMNH-PL). 177466 records from CAS Entomology (ENT). 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 73 records from VFD-HH/SH: Pferdweide Lammert. 22 records from Phytoplankton abundance at bottle station GOM6/1. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 53643 records from CESJ - Herbário Leopoldo Krieger. 11 records from Zoobenthos in surface sediments off Cape Lucul. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 6 records from Wiese. 3 records from Nannofossil abundance of Hole 94-609A. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 423 records from Bird Collection of Otto Hedin. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 274 records from Foraminifera abundance of sediment core BM1958.631. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 68 records from Planktic foraminifera abundance of Hole 22-213. 126 records from Planktic foraminifera abundance of Hole 32-305. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 97 records from CNIN/Tipos Hymenoptera. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 3 records from Analyses of the recent components of sediment core PS1215-2. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 3204 records from Faunal Inventory of Morysin Nature Reserve. 1770 records from Schmidt Museum of Natural History_Birds. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 19 records from Occurrence of mammalia relicts at site Gröbern. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 169 records from Whale log - observations from ANARE voyages. 2 records from Abundance of benthos infauna at station GIK23025-2. 99159 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 1 records from Zetes latirostris. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 101 records from MVZ Mammal Observations (Arctos). 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 117 records from Wassermann. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 105 records from BIRDRACE coesfelder_vogelkundler. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 268876 records from Fiji Terrestrial Arthropods. 89762 records from Ornitho.eus. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 9719 records from The Orchid Atlas of Western Australia. 875 records from Fish monitoring data in Lake Kasumigaura. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 252060 records from Moths Ireland. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 61 records from Fürstenberger Ralley Teil 3. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 106100 records from Fish (NSMK-PI). 921 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 31082 records from MEXU/Plantas Vasculares. 8980 records from MEXU/Tipos de plantas vasculares. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 29 records from Klimaoasen in Köln. 46 records from An der Ohm, (Wettsaasen). 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 21795 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 82953 records from Vascular Plants, Observations, Oslo (O). 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 257 records from Kernberge und Umgebung (Jena). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 83 records from Planktic foraminifera abundance of Hole 14-135. 2357 records from Foraminifera abundance of Hole 17-167. 163 records from Planktic foraminifera abundance of Hole 32-313. 525 records from Planktic foraminifera abundance of Hole 94-609. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 18039 records from Sponges of Rathlin Island. 258638 records from R. L. McGregor Herbarium Vascular Plants Collection. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 1 records from Zetes semirufus. 1351 records from Neogene palynomorpha from site 93-603, part 1. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 1 records from Miriapodi di alcune grotte della Campania. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 35 records from Gym Freyung. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 18 records from Meiofauna abundance in sediment core 13368-015. 308 records from Planktic foraminifera counts of sediment core V19-178. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 85783 records from Birds (KIEE-BI). 165299 records from CAS Invertebrate Zoology (IZ). 31 records from Liether Park (LMS), 6g. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1 records from Planktic foraminifera abundance of Hole 8-72. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 232734 records from MVZ Mammal Collection (Arctos). 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 28 records from Occurrence of mammalia relicts at site Climauti II. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 70 records from Exotic terrestrial flatworms, Macquarie Island. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 1798 records from Insect (KDIR-IN). 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 119366 records from The digitization of plant specimens of NTU. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 101 records from Birdrace-Herford-Birder-Herford. 15 records from AKG-Bensheim. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 2 records from Amphibia ZMK. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 30 records from Benthic foraminifera abundance of Hole 42-379A. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 881 records from Moluscos Marinhos de Augusto Nobre. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 18389 records from Mycology Herbarium, Trondheim (TRH). 14202 records from Plant specimens of Hokkaido University Museum. 13736 records from MfN - Mallophaga Collection. 648 records from Korea Bird Distribution Atlas Database. 37641 records from Nordic Genetic Resources. 3634 records from Herpetological collection of National Museum of Nature and Science. 13478 records from Herp Collection. 53 records from Planktic foraminifera abundance of Hole 29-281A. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 398 records from Mooswald (Freiburg). 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 66 records from Foraminifera abundance of Hole 55-432A. 11 records from Collection Xiphosura SMF. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 73 records from Fossil (JNHM-FO). 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 131 records from Unser Schulhof - eine Apotheke. 3941 records from UAFMC Mammals. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 1 records from Results of palynological analysis of Hole 302-M0004C. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 10121 records from Arachnologie - SMNG. 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 64 records from Feuchtbiotop Weidenkaule. 2 records from Kirchenforst. 30 records from Nannofossil abundance of Hole 8-71. 115 records from Nannofossil abundance of Hole 29-279A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 271 records from Planktic foraminifera counts of sediment core RC11-147. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 3761 records from Mountain Invasion Research Network (MIREN) survey. 998 records from Korean Ethnobotany Database. 30302 records from Arizona State University Amphibian and Reptile Collection. 448 records from Harpactus Shuckard. 48 records from Freiheitsring (Frechen). 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 4 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 1 records from Zetes ephippiatus. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 906 records from Digital Florula - Las Cruces Biological Station. 97 records from LauWi. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 20 records from Mikroorganismen. 114 records from BIRDRACE VIE will rock you!. 48 records from Wahner Heide LK 12 Biologie. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 72 records from Faunal assemblage of sediment core TR149-35. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 1726 records from KTU Pinophyta. 22 records from Nannofossil abundance of Hole 9-83A. 21 records from Nannofossil abundance of Hole 24-232A. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 56 records from Nannofossil abundance of Hole 94-607. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 12 records from Ficha de Sonora aemula. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 5159 records from CNHE/Coleccion Nacional de Helmintos. 22 records from Sediment properties of core PLG95B_06BOXG. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 2233 records from Chrysomelidae of Poland. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 9 records from Nannofossil abundance of Hole 60-455. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 107 records from Landschaftsschutzgebiet Buchhorst 3. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 5 records from Analyses of the recent components of sediment core PS1400-4. 2128 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 90 records from Schulhof Bühlschule Giengen. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 13 records from Collection Reptilia fossil SMF. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 2324 records from Eriophyoid Mites of Poland. 836971 records from Bernice P. Bishop Museum. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 4303 records from Odonata Collection. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 372 records from Colección de Entomología - Arthropoda. 416644 records from Entomology, Natural History Museum, University of Oslo. 84521 records from BioGIS - Vascular plants - INPA database. 160 records from Wirbach-Taubental (Bad Blankenburg). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 7076556 records from Great Backyard Bird Count. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 11708 records from The Erysiphales Collection at the Botanische Staatssammlung München. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 241 records from Planktic foraminifera abundance of Hole 67-499B. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 52 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 5733 records from Small Mammal Research Database. 84 records from BIRDRACE Birding for Nature. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 6 records from Nannofossil abundance of Hole 7-63. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 76 records from Coccoliths in sediment core PS1533-3. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 24. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 1069 records from ZFMK Sound Archive. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 19821 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from Notizen über Oribatei (Acari). III. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 46400 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 778 records from Planktic foraminifera abundance of Hole 40-362. 531 records from Collection Crustacea - KAUMM. 12 records from Abundance of radiolaria at station LV28-40-2. 1130 records from Ostracoda in sediment core PS51/154-11. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 256 records from BIRDRACE Upupa epöpse. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 1761 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 56302 records from Kathryn Kalmbach Herbarium. 47 records from Schulgelände Ceciliengymnasium. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 94 records from Coccolith counts of multinet SO119_MSN1298. 19 records from Nannofossil abundance of Hole 31-298. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 48 records from Trockenrasen bei Dörndorf. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 70 records from Parkuntersuchung Weißer See. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 32762 records from Fish tag database. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 774 records from Planktic foraminifera abundance of Hole 80-549A. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 103 records from BIRDRACE Die Otzberger. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 57 records from Nannofossil abundance in sediment core PS1311-4. 315 records from Planktic foraminifera counts of sediment core RC17-69. 254 records from BIRDRACE Thüringer Becken-Birders. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 109176 records from Herps Specimens. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 17980 records from Impetus - Herbarium Hamburgense. 6 records from Sediment properties of core PLG93_BCORE1. 302 records from Stadtpark Sulzbach-Rosenberg. 168 records from Weidenhüttendorf an der Würm (München). 1 records from Planktic foraminifera abundance of Hole 54-420A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 4051 records from Homoptera. 1418 records from Fossil (GNHM-FO). 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1709819 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 1028827 records from SEAMAP - marine mammals, birds and turtles. 93 records from CCUG Microorganisms databases(Fungi). 54059 records from Pelagic Fish Observations 1968-1999. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1853 records from Yeast Collection in BCRC. 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 66 records from Mammals (KIEE-MM). 5549 records from Diplopoda (NSMK-DI). 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 1 records from Hausgarten. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 25471 records from Ibaraki Nature Museum, Arthropoda collection. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 2880 records from Coleoptera, NEF. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 1294 records from Global Butterfly Information System (GloBIS). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 88 records from Total foraminifera counts of multinet SO118_MSN1265. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 19 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 1 records from Nothrus biverrucatus. 6062 records from Lichens of Knyszyn Forest. 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 184156 records from The Flora of County Waterford. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 1 records from Zetes cespitum. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1201 records from monocotyledonous_geophytes_of_fergana_valley. 588 records from Relative abundance of ostracods in sediment core Lz1120. 107 records from BIRDRACE Herford Birders. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 86 records from Fliegenhaupt Marksuhl. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 74 records from SuLaMa reptile monitoring. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 34586 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 1356 records from Collection Crustacea ZMG. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 320 records from Myxomycetes collection of the University of Eastern Finland. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 99 records from Planktic foraminifera abundance of Hole 94-610E. 25 records from Benthic foraminifera abundance of Hole 1-4. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 145 records from privater Garten. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 356 records from Biotope in Rheine - Aktion 350. 177 records from Donauinsel des BN bei Entau. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 279 records from Planktic foraminifera abundance of Hole 11-98. 91 records from Benthic foraminifera abundance of Hole 84-569A. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 13646 records from Senckenberg - CeDAMar Resource. 53985 records from BioMar - LIFE project. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 441 records from Pollen analysis of surface samples from Germany and Austria. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 93 records from Südwestlich der Parkwiesen. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 107 records from Planktic foraminifera abundance of Hole 18-180. 2 records from Benthic foraminifera abundance of Hole 42-376. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 19093 records from West African Vegetation Database. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 30985 records from MEXU/Asteraceae. 265 records from CNIN/Mantodea. 176 records from INSECT COLLECTION. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 3483 records from Irish National Frog Database. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 10885 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 1 records from Pollen and spore abundance of Hole 42-379A. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 8 records from UWYMV Herpetology Collection (Arctos). 201 records from Mammals in MZNA-VERT: project CAS. 2839 records from Rocky Shore Macroalgae. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 77 records from Total foraminifera counts from M35/1_MSN1075. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 3 records from Antarctic Arrow worms. 9728 records from Birds of Ireland. 7966 records from MfN - Phasmid Collection. 5 records from Memorial University Botanical Garden Collection. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 107 records from 1st Austrian Birdrace (Wien). 44 records from Flora und Fauna in unserer Kita. 7938 records from Hymenoptera collection, Natural History Museum, University of Oslo. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 144 records from BIRDRACE Punkbirder Helgoland. 1729 records from Biodiversidad de Datura (Solanaceae) en México. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 3978 records from Colección de Entomopatógenos de México (CNRCB). 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 12 records from Abundance of radiolaria at station LV28-44-1. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 6 records from Nannofossil abundance of Hole 55-430B. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 54 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 492 records from Verneplan Hjerkinn karplanter. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 214 records from Binsenwiesen. 87 records from Klütwald. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 2 records from Nothrus palustris. 679 records from Results of palynological analysis of Hole 302-M0004A. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 6394 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 19557 records from Collection Thysanoptera SMF. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 3 records from Mammalia (SMNH-MM). 1 records from Celaeno spinosa. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 5 records from Streuobstwiese (Mittelgasse 4). 57 records from Garten in Schmölln. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 7427 records from Weevils of the Tatra Mts.. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 1826 records from Collection des Mollusques (BOUM). 153 records from Selztal bei Friesenheim. 18 records from Landschaftsschutzgebiet Buchhorst2. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 4 records from Estimated plankton abundance at station PS63/064-6. 49637 records from Monitoring data from the federal state Hesse (Germany). 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 20973 records from Real Jardin Botanico, Madrid: MA-Funhist. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 1042 records from Planktic foraminifera abundance of Hole 37-333. 8 records from Pollen and spore abundance of Hole 42-380. 36613 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 2 records from Nannofossil abundance of Hole 6-49. 30008 records from Lepidoptera specimen database of Japan. 127 records from Collection Hydrozoa - ZMB. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 141 records from Schulhof und Anlagensee in Nellingen. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 83042 records from UPCB - Herbário do Departamento de Botânica. 5391010 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 39586 records from MSB Bird Collection (Arctos). 347 records from (Table 4) Standing stock values of important species in surface sediments. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 45 records from Nannofossil abundance of Hole 28-265. 21 records from Meiofauna abundance in sediment core 13077-006. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 8649 records from Fossil (WSHN-FO). 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 117 records from Muskox Abundance. 1 records from Planktic foraminifera abundance of Hole 8-73. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 343 records from Collection Cnidaria - ZMB. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 2088 records from Benthic foraminifera of sediment core MD99-2286. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 154124 records from Arizona State University Lichen Collection. 41460 records from Herbarium (UNA). 57 records from Occurrence of mammalia relicts at site Moladova V. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 246 records from Benthic foraminifera abundance of Hole 73-524. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 6987 records from National Trust - Ickworth species data held by The National Trust.. 1 records from Damaeus auritus. 1 records from Flora of Suriname, volume VI, part I. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 300 records from Gunma Museum of Natural History, Fish Specimen. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 764 records from BioGIS - Fish - INPA database. 11268 records from Aphidoidea Collection. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 6422 records from Ájtte. 190515 records from Mycology herbarium, Oslo (O). 5 records from Rediscovery and redescription of Centrodora damoni (Girault) (Hymenoptera: Aphelinidae) from Australia, an egg parasitoid of Gonipterus spp (Coleoptera: Curculionidae), after nearly a century. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 8640 records from Fossil (WSHN-FO). 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 20847 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 365 records from Colección Herpetológica de la Patagonia. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 352 records from Universidad de Málaga: MGC-Lichen. 8 records from Krittenhorster Wald (Ostkilver). 193 records from Total foraminifera counts of multinet M21/3_MSN663. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 22 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 1303 records from Mid Ulster Hare Surveys 2012-2015. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1952 records from ISM Ichthyology Collection. 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 145 records from Phytoplankton abundance at station CD46_0405C#7. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 921 records from Planktic foraminifera counts of sediment core RC14-37. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 5995 records from Insect (HUNM-IN). 47499 records from Sphaeroceridae Collection. 133656 records from NINA insect database. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 114 records from BIRDRACE Di-Bi-Di-Birder. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 1023 records from Spencer Entomological Museum. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 296 records from DJH. 2148 records from Eppingen und Umgebung. 269 records from 3. Tag der Artenvielfalt Hockenheim. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 15 records from Spiders of the genus Habrocestoides from China (Araneae: Salticidae). 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 3982 records from Plant (GFEI-PL). 27828 records from svalbardflora.net. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 426 records from Myriapoda - SMF. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 1154 records from Collection Plecoptera - SMF. 313162 records from Observational database of Icelandic plants. 2483 records from Bacteria collection of National Institute of Public Health, Poland. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 767 records from BioGIS - Bats - Asaf Tsoar database. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 56250 records from Fish Specimens. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 759 records from Planktic foraminifera abundance of Hole 47-398D. 878 records from Planktic foraminifera abundance of Hole 84-568. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 86 records from Pollen analysis of sediment core GIK16856-2. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 6 records from Planktic foraminifera abundance of Hole 23-226. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 76 records from Occurrence of mammalia relicts at site Vindija. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 11 records from Observation of birds at station PS14/156 along 49° West. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 50 records from Lindesnes. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 30 records from Leben auf einer Sturmfläche. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 84 records from North Carolina State Museum of Natural Sciences Fishes Collection. 599 records from NHT flora. 10567 records from Coleoptera collection of National Museum of Nature and Science. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 27 records from Zwickau- Schwanenteich. 163 records from Tiere und Pflanzen am Pfannenbach. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 1 records from Pelops phaeonotus. 1 records from Diatom abundance of Hole 95-613. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 87 records from Total foraminifera counts of trap L2_92_B49. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 4 records from Nannofossil abundance of Hole 29-281A. 14 records from Nannofossil abundance of Hole 85-573. 28 records from Nannofossil abundance of Hole 26-253. 18 records from Meiofauna abundance in sediment core 13200-012. 316 records from Planktic foraminifera counts of sediment core V14-101. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 190 records from Foraminifera abundance of sediment core MD81-LC07. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 81329 records from natagora-earlybirds. 820552 records from Fauna Atlas N.T.. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 190 records from ENBI-Dataset of GART-GloBIS. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 25372 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 190 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 281250 records from Quadrige. 27264 records from Formidabel; Belgian Ants Database. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 11 records from Nannofossil abundance of Hole 6-56B. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 692 records from Planktic foraminifera abundance of Hole 40-360. 2034 records from Herbarium of Namur. 5 records from Tuttlinger Tag der Artenvielfalt. 39033 records from SBMNH Vertebrate Zoology. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 3 records from Analyses of the recent components of sediment core PS1215-2. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 73 records from Planktic foraminifera abundance of Hole 2-11. 70 records from Planktic foraminifera abundance of Hole 84-569A. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 46 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 26368 records from Marie-Victorin Herbarium (MT) - Bryophytes. 18 records from Planktic foraminifera abundance of Hole 32-310. 94 records from Planktic foraminifera abundance of Hole 80-550. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 72636 records from Insect Collection of Taiwan Forestry Research Institute. 7 records from Additions to the myxobiota of the Åland Islands. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 356 records from Morphologische Daten von Puffinus creatopus. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 25128 records from rmca-albertine-rift-butterflies. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 1 records from Abundance of benthos infauna at station GIK23004-3. 350140 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 3621 records from Millenium Seedbank (MSB). 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 244 records from WildesMoor bei Schwabstedt. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 3 records from Nannofossil abundance of Hole 51-417D. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 923 records from Collection Graptolithina fossil SMF. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 4 records from Arthropoden aus südostalpinen Höhlen.. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 99 records from Düne am Ulvenberg (Darmstadt). 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 1965 records from Global caridean shrimp fauna. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 4024 records from Sightings Map of Invasive Plants in Portugal. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 86556 records from NINA Vanndata øvrige arter. 20 records from Motzener Tonsee. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 26 records from Ostracoda abundance of Hole 13-132. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 143763 records from University of British Columbia Herbarium (UBC) - Algae Collection. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 45 records from Parcela Permanente en el Pantano Martos. 264743 records from ArtenFinder. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 237 records from RSPB - Capercaillie national surveys (SCARABBS). 16 records from Dinoflagellate cysts of surface sediments. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 504 records from Shellfish (JNHM-MS). 133 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 60000 records from Birds (NSMK-BI). 11981 records from SMNK Mantid Collection. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 91 records from CNIN/Tipos Homoptera. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 1251 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 92 records from Siliceous microfossil occurrence, Site 177-1094. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 464 records from Lepidoptera collection, NTNU, Trondheim. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 1078 records from Fishes of the Congo River 2010 Expedition. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 377096 records from University of Florida Vertebrate Paleontology. 9948 records from Bees of Canada / Gschwendtner property collection. 1863 records from Cowan Tetrapod Collection - Herpetology. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 1030627 records from Phanerogamic Botanical Collections (S). 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 221558 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 718 records from HSU Vertebrate Museum Amphibian Collection. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 84 records from BIRDRACE Vogelscheuchen. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 66 records from Range table from ostracoda in ODP Hole 151-910D. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 527 records from Inventaire floristique de Beza Mahafaly. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 104 records from Total foraminifera counts of multinet M21/6_MSN778. 65535 records from OAC-BIO Herbarium. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 54 records from Wiese am Unterbecken. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 16 records from Nannofossil abundance of Hole 47-398B. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 34506 records from Herbarium de Geo. B. Hinton, México. 155 records from Bergbaufolgelandschaft am Muldestausee. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 27 records from Benthic foraminifera abundance of Hole 34-320A. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 14 records from Collection Pantopoda SMF. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 8 records from Abundance of radiolaria at station LV28-29-1. 36845 records from MfN - Fossil invertebrates Ia. 2 records from Smear slide analysis of sediment core GeoB7427-2. 2 records from Nannofossil abundance of Hole 74-526. 104 records from Ross Sea Pycnogonids. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 6 records from Ökosysteme rund um Wedel. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 588 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 8 records from Occurrence of mammalia relicts at site Wretton. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 47289 records from Naturalis Biodiversity Center (NL) - Porifera. 9123 records from Flora of Słowiński National Park, Poland. 1447 records from Odonata of the Congo River 2010 expedition. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 15 records from Herdengelhoehle taxa and datings. 2083 records from Planktic foraminifera abundance of Hole 72-517. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 102 records from Ostracod abundance in sediment core Lz1120. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 3015 records from Bird specimens in Gifu Prefectural Museum. 131 records from Artenvielfalt auf dem Schulgelände. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 1549 records from mushroom. 741 records from Planktic foraminifera abundance of Hole 20-200. 93712 records from Herbarium of Umeå University (UME). 535 records from Benthic foraminifera abundance of Hole 73-522. 2107 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1627 records from The Irish Squirrel Survey 2007. 2894 records from Insect (SMNH-IN). 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 1990 records from Seabird 2000. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 6381 records from UPRM Invertebrate Collection. 241 records from BIRDRACE RennVögel Münsterland. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 7950 records from European riparian ground beetles. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 1 records from Arthropoden aus südostalpinen Höhlen.. 13968 records from NYSM Birds. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 112 records from BIRDRACE Gütersloher Gimpel. 67 records from Tongrube bei Hettstedt. 57 records from Schulgarten Janusz-Korczak-Realschule. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 777 records from Planktic foraminifera counts of sediment core RC17-108. 1000 records from Plant (KOBG_PL). 349988 records from BSBI tetrad data for Ireland. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 11054 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 520 records from Planktic foraminifera abundance of Hole 39-357. 44 records from Planktic foraminifera abundance of Hole 19-188. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 102 records from Benthic foraminifera abundance of Hole 42-372. 19 records from Dinoflagellate abundance of Hole 81-553A. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 1 records from Antarctic Marine Amoebae. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 11370 records from Distribution of planktic foraminifers of core V22-174. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 13702 records from Fundación Miguel Lillo - Colección Ornitológica. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 180 records from Range table from ostracoda in ODP Hole 144-871A. 2050 records from Birds (ENHM-BI). 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 4100 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 73544 records from Marsh Monitoring Program - Birds. 1833 records from DSMZ Fungi. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 3343 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 45 records from Wasser-Lernort Nettemündung. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 7 records from Boraginaceae (Cynoglossum cherangauiense). 24 records from Occurrence of mammalia relicts at site Overmere. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 1 records from Microfossil abundance of Hole 42-378. 2387 records from The French Collection of Medicago truncatula. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 9933 records from CHAS Mammalogy Collection (Arctos). 100 records from Birdrace-The_Ringers-Friesland. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 1634 records from ZFMK DORSA. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 1 records from Abundance of benthos infauna at station GIK23062-2. 1 records from On the Chilopoda from Turkey. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 2 records from Porifera ZMK. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 96 records from Birdrace-federleser-Herford. 57 records from Heidesee / Halle. 147 records from NABU-Auerochsenweide. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 41 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 1 records from Nothrus scaliger. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 11431 records from Herp Specimens. 1000 records from Diplopoda (JJHA-DI). 8684 records from Individual Sightings. 2241402 records from Biologiezentrum Linz. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 498 records from Dinoflagellate abundance of Hole 94-611C. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 485 records from UAM Herpetology Collection (Arctos). 5262 records from Spider Mites Collection of Jean Gutierrez. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 1733 records from Birds collection of Abiko City Museum of Birds. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 1409 records from Planktic foraminifera counts of sediment core AB000280. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 212 records from Nanoplankton abundance at station GeoB2017-1. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 349 records from Planktic foraminifera counts of sediment core V20-170. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 23146 records from BC Coastal Waterbird Survey. 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 94474 records from TNHC Herpetology Collection. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 42 records from Foraminifera abundance of Hole 24-236. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 13733 records from Collection Bryozoa SMF. 139 records from Siliceous microfossil occurrence, Site 177-1093. 14532 records from MVZ Egg and Nest Collection (Arctos). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 1 records from Nouvelles fourmis d'Afrique.. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 255 records from GENT Lactarius Deliciosi. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 91 records from BIRDRACE SchrägeVögel. 76 records from Faunal assemblage of sediment core GS7603-10. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 167 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 5429 records from Ibaraki Nature Museum, Algae collection. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 172 records from Foraminifera abundance of Hole 59-448A. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 31030 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 294 records from Naturgarten Langenholtensen. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 9 records from Nannofossil abundance of Hole 1-2. 36 records from Nannofossil abundance of Hole 14-141. 753 records from Planktic foraminifera counts of sediment core V28-127. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 478 records from EASIANET. 212930 records from KU Museum of Invertebrate Paleontology. 15 records from Pogonophora collection of National Museum of Nature and Science. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 39615 records from Irish vascular plant data 1999-2009. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 1998 records from Aves de la cuenca media del río Bogotá. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1 records from Nothrus pollinosus. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 6717 records from LSUMZ Mammal Tissues. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 596 records from Planktic foraminifera counts of sediment core A15-558. 169 records from Planktic foraminifera counts at CTD station PS55/051. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 7 records from Nannofossil abundance of Hole 38-336. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 2000 records from Shellfish (ASJK_MS). 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 5205 records from Botanical Garden Collection. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 35 records from Nannofossil abundance of Hole 78-543. 6 records from Nannofossil abundance of Hole 6-49. 591 records from Planktic foraminifera counts of sediment core V16-25. 2792 records from Birds (UWEP-BI). 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 751594 records from Royal Botanic Garden Edinburgh Herbarium (E). 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 24121 records from Endemic plants of the Congo basin. 50128 records from Tasmanian Museum and Art Gallery provider for OZCAM. 85 records from Birdrace-Die_Paradiesvögel-Herford. 3 records from Blankenfelder See. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 1421 records from Weevils of Poland. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 5 records from Schulwald Regionale Schule Sprendlingen. 9 records from Coccolith counts of multinet M32/5_MSN982. 2073 records from Bryophyte collection of Jyväskylä University Museum. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 7503 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 6627 records from ATCC Fungi Collection Catalog. 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1101 records from Relative abundance of ostracods in sediment core Co1202. 19 records from Microplankton data off Mejillones, 2006, Chile. 371 records from Planktic foraminifera abundance of Hole 63-470. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 718087 records from Insect (KNAM-IN). 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 7637 records from Mammals Specimens. 200390 records from Mammalogy Collection - Royal Ontario Museum. 1298 records from Planktic foraminifera abundance of Hole 23-219. 84 records from Benthic foraminifera abundance of Hole 84-566C. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 8977 records from CRI - Herbário Pe. Dr. Raulino Reitz. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 39 records from Red list project inventory, fungi. 17 records from Hazel Dormouse in Ireland. 98287 records from CAS Ornithology (ORN). 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 33 records from Schüler erforschen die Helme-Aue. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 8 records from Nannofossil abundance of Hole 49-409. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 1301 records from Collection Hymenoptera SMF. 495 records from Life Science National Tsing Hua University. 7 records from Analyses of the recent components of sediment core PS1219-1. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 38 records from Microfossil abundance of Hole 21-206C. 1 records from Dinoflagellate abundance of Hole 19-183. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 6 records from Mammalia (JNHM-MM). 65 records from BIRDRACE Federal Birds of Investigation FBI. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 12 records from Nannofossil abundance of Hole 20-200. 129 records from Nannofossil abundance of Hole 29-284. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 1794 records from Herbarium BSG Lichenes. 76253 records from Irish Vascular Plant Data - Paul Green. 16 records from Nannofossil abundance of Hole 9-77B. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 15 records from Occurrence of mammalia relicts at site Dendermonde. 63646 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 7992 records from UWBM Herpetology Collection (Arctos). 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 10075 records from Nematoda of Costa Rica (INBio). 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 1 records from Zetes morticinus. 43 records from Schulgelände Thurmair-Gymnasium. 95 records from Vielfalt verschiedener Wiesen. 504 records from Schatzinsel Wangerooge. 248 records from Schulgarten der Volksschule. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 260 records from Range table from ostracoda in ODP Hole 144-873B. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 30000 records from Freshwater Fish Specimens of Lake Biwa Museum. 8523 records from Distribution of planktic foraminifers of core RC24-16. 1458 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 90 records from Collection Ctenophora SMF. 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 15000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 239 records from Naturerlebnisraum Koppelsberg. 1 records from Nothrus theleproctus. 186 records from Planktic foraminifera abundance of Hole 94-610. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 350 records from Speothos Venaticus por Guillermo Gil. 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 50 records from Planktic foraminifera abundance of Hole 60-457. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 7848 records from Lichen specimen database of Faurie collection. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 89 records from Total foraminifera counts of multinet M10/2_MSN298. 22 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1337. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 4085 records from SMNS Palaeontological collection - Tertiary mammals. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 2071933 records from Museum of Comparative Zoology, Harvard University. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 233 records from Föhrenried (Fronreute und Baindt). 58 records from Total foraminifera counts of multinet M27/2_MSN882. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 783 records from Phytoplankton abundance in surface water during cruise CD61. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 7 records from Nannofossil abundance of Hole 5-33. 14 records from Nannofossil abundance of Hole 8-72A. 5 records from Nannofossil abundance of Hole 84-569. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 3 records from Nannofossil abundance of Hole 22-212. 15 records from Microfossil abundance of Hole 59-450. 4 records from Nannofossil abundance of Hole 52-418. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 907 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 1293 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 7 records from Nannofossil abundance of Hole 9-82A. 775 records from Insect (GNHM-IN). 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 1272 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 233 records from Total foraminifera counts from M35/1_MSN1044. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 62 records from Total foraminifera counts of multinet M42/3_MSN1366. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 2299 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 41 records from Altholzparzelle Eilenriede Hannover. 125 records from Artenbestimmung. 3 records from Planktic foraminifera abundance of Hole 54-424B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 6058 records from Spider (YCEM-SP). 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 56 records from Estetal (Buxtehude). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 149 records from Bayerische Donau - Neu Ulm. 238 records from Coccoliths in ODP Hole 104-643A. 593 records from Ostracoda in sediment core PS51/159-10. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 6987 records from Lyman Entomological Museum. 15886 records from Insect Specimen Database of Fukui City Museum of Natural History. 19164 records from The Gordon Alexander Orthoptera Collection. 3 records from Acari fossil - SMNG. 94 records from Planktic foraminifera abundance of Hole 32-310. 325 records from Planktic foraminifera abundance of Hole 32-305. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 308 records from Wangerooge. 368 records from Great Lakes Forestry Centre Insect Collection. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 354 records from Foraminifera distribution of sediment core KS310. 164 records from Planktic foraminifera abundance of Hole 94-610B. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 1 records from Pelops fuligineus. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 4761 records from SMDB - Santa Maria Departamento de Biologia. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 92 records from The Ants of Bulgaria. 16246 records from Herbarium Erlangense. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 360 records from Order Araneae. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 15 records from Kühnauer Aue und Kühnauer See. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 80 records from BB-Biodiversität b. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 317 records from Planktic foraminifera counts of sediment core RC14-29. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 32 records from Nannofossil abundance of Hole 67-499. 3 records from Nannofossil abundance of Hole 9-80. 2 records from Nannofossil abundance of Hole 29-280A. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 703 records from Planktic foraminifera counts of sediment core V25-59. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 4244 records from Insect Specimens of Lake Biwa Museum. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 60 records from Planktic foraminifera abundance of Hole 19-192. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 96 records from Guadeloupe_manguier. 89 records from Birdrace-Team_Wangerooge-Friesland. 28 records from Stadtpark Prinzengarten (Sigmaringen). 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 122 records from Phytoplankton abundance at station CD46_1005C#4. 316 records from Planktic foraminifera counts of sediment core RC11-86. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 16 records from Abundance of radiolaria at station LV28-3-3. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 35 records from Ortsrand Zandershagen. 46 records from Antarctic Isopods. 34253 records from MedOBIS (EurOBIS). 1 records from Berlese's Primitive Oribatid Mites. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 353 records from Stadtgebiet (Dannenberg). 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 19127 records from Biological Records Centre - Cerambycidae Dataset. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 1489 records from Herbarium Rhoenmuseum Fladungen. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 21261 records from Sukkulentensammlung Zürich. 1 records from Nothrus pulverulentus. 40 records from Tiere und Pflanzen um uns herum !. 85 records from Sedimentological investigation on core V25-45. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 2 records from Nannofossil abundance of Hole 7-64A. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 175 records from Neißetal. 692 records from Collection Trilobita SMF. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 230221 records from UA Herbarium. 2199 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from H. Sauter's Formosa-Ausbeute: Formicidae (Hym.).. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 1020 records from Irish Marine Turtle Database. 100 records from Grenzturm Hohen Neuendorf. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 1 records from Nothrus posticus. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 135 records from Waldi-Weiher. 269 records from BIRDRACE Dithmarscher Deichhühner. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 180 records from Paul-Gerhardt-Schule Dassel. 5 records from Fledermäuse u. nachtaktive Insekten. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 482 records from Kühmark bei Wetzlar. 31 records from Nannofossil abundance of Hole 4-23. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 48 records from Benthic foraminifera abundance of Hole 42-380A. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 47 records from Lepidurus arcticus survey Northeast Greenland 2013. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 581051 records from Swiss National Butterflies Databank. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 508 records from Guyane_Cacaoyer. 2863 records from Invertebrates compiled by W.Block. 2 records from List of the specimens of dipterous insects in the collection of the British Museum. 185 records from Abundance of coccosphere-units of site GIK23414. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 23 records from Landwehrbach. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 1386 records from Red list project inventory, lichens. 92 records from Nottekanal, Klasse 7 - 10. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 892 records from Weevils of Wales and England. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 20043 records from Mollusca collection of National Museum of Nature and Science. 192458 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 58 records from Lüner Holz (Lüneburg). 203 records from Planktic foraminifera abundance of Hole 72-515B. 525 records from Benthic foraminifera abundance of Hole 40-360. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 1 records from Papilio Sticheli nov. spec. aut subsp.. 60 records from Schafsweide Seniorenhaus Berghof. 76 records from BIRDRACE Nachtigallen. 704 records from Planktic foraminifera counts of sediment core V18-207. 1148 records from Southern Ocean Ostracoda (except Halocypridina). 12 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 691 records from RSPB - Black grouse national surveys (SCARABBS). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 22745 records from HRCB - Herbário Rioclarense. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 1 records from Nothrus bicarinatus. 7551636 records from BirdLife Australia, Birdata. 8629 records from National Taiwan University. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 12 records from Art´n Vielfalt im Kinderwald. 198 records from Total foraminifera counts from M35/1_MSN1047. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 483 records from Artenvielfalt im Rhein-Neckar-Raum. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 9 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 22041 records from CUMV Mammal Collection (Arctos). 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 181 records from Alien Species in Poland - Animals. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 102 records from Birdrace-OAG_Neuwerk-Hamburg. 61 records from BIRDRACE Baumläufer. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 2654 records from Collection of Hymenoptera. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 1 records from Celaeno detrita. 7346 records from MfN - Fossil vertebrates III. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 42 records from Chaetognatha - SMF. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 786 records from Planktic foraminifera abundance of Hole 72-518. 10 records from Oberservation of birds at station PS14/143 along 49° West. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 69 records from Mönchspark. 92 records from Nannofossil abundance of Hole 31-296. 4 records from Range table from nannofossils in ODP Hole 139-857A. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 4 records from Nannofossil abundance of Hole 16-156. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 31 records from Bayerische Donau - Tapfheim. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 20 records from Nannofossil abundance of Hole 7-63A. 7 records from Nannofossil abundance of Hole 27-259. 14 records from Nannofossil abundance of Hole 14-140. 90 records from Planktic foraminifera counts of sediment core RC13-158. 63 records from Planktic foraminifera counts of sediment core V19-21. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 8336 records from Birds (GMBO-BI). 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 27 records from Pollen data of trap CB3. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 15675 records from Institut Botanic de Barcelona, BC-Histórico. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 191 records from Foraminifera abundance of sediment core C1960.202. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 429 records from Larval fish at Helgoland Roads in 2004. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 5634 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 35548 records from Herpetology. 5 records from Analyses of the recent components of sediment core PS1216-1. 11831 records from UCM Bird Collection (Arctos). 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 1 records from Oribates ovalis. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 57 records from Schulgarten Fichteschule. 15 records from Urwald 2 (Bad Waldsee). 171 records from Sahrbachtal Kreis Ahrweiler. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens
Keywords: GBIF; biodiversity; species occurrences